2017
DOI: 10.1002/sctm.17-0134
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Mesenchymal Stem Cell Therapy for Acute Liver Allograft Rejection

Abstract: Acute allograft rejection remains common after liver transplantation despite modern immunosuppressive agents. In addition, the long‐term side effects of these regimens, including opportunistic infections, are challenging. This study evaluated the safety and clinical feasibility of umbilical cord‐derived mesenchymal stem cell (UC‐MSC) therapy in liver transplant patients with acute graft rejection. Twenty‐seven liver allograft recipients with acute rejection were randomly assigned into the UC‐MSC infusion group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 33 publications
(43 reference statements)
0
84
0
Order By: Relevance
“…Patient populations were diverse and included cardiovascular (12 trials, n = 612 patients) [21,24À27,29,37,40,42,44,49,58], neurological (10 trials, n = 242 patients) [30À32, 36,45,48,57,62,65,69], renal (three trials, n = 177 patients) [55,63,67], liver (seven trials, n = 404 patients) [35,43,47,53,54,59,66], respiratory (three trials, n = 134 patients) [18,23,68] and endocrine diseases (four trials, n = 169 patients) [22,28,39,50], hematological/oncological malignancies (five trials, n = 318 patients) [33,34,41,46,71], immune deficient or inflammatory conditions (nine trials, n = 544 patients) [20,38,51,52,60,61,64,70,72], general frailty (one trial, n = 30 patients) [56], and severe sepsis in severely neutropenic patients with hematologic malignancies (one trial, n = 30 patients) [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient populations were diverse and included cardiovascular (12 trials, n = 612 patients) [21,24À27,29,37,40,42,44,49,58], neurological (10 trials, n = 242 patients) [30À32, 36,45,48,57,62,65,69], renal (three trials, n = 177 patients) [55,63,67], liver (seven trials, n = 404 patients) [35,43,47,53,54,59,66], respiratory (three trials, n = 134 patients) [18,23,68] and endocrine diseases (four trials, n = 169 patients) [22,28,39,50], hematological/oncological malignancies (five trials, n = 318 patients) [33,34,41,46,71], immune deficient or inflammatory conditions (nine trials, n = 544 patients) [20,38,51,52,60,61,64,70,72], general frailty (one trial, n = 30 patients) [56], and severe sepsis in severely neutropenic patients with hematologic malignancies (one trial, n = 30 patients) [19].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to MSC preparation and administration, of the 55 included RCTs, 31 (56¢4%) examined bone marrow [19,21-27,29-34,36,39,41-43,45,47,53,55À59,61,66,68,71], 16 (29¢1%) umbilical cord [28,35,38,40,44,46,[48][49][50][51][52]54,60,63,65,72], four (7¢3%) adipose-derived MSCs [18,20,62,64], two (3¢6%) placenta-derived cells [69,70]; and in two RCT (3¢6%) the source of MSCs was unclear [37,67]. See Supplementary Table 1 [33,34,41,67].…”
Section: Resultsmentioning
confidence: 99%
“…The other concern is that MSC not only has potential to inhibit tumor immune responses, but also can generate new blood vessels, which may promote tumor growth and metastasis [52]. Although MSC has shown great promise in the treatment of some immunological diseases (especially GVHD), the variabilities of MSC quality from different donors and tissues are widely varies, and treatment protocols, doses and injection modes are inconsistent during experimental procedures [53]. All these factors may limit the therapeutic effect of MSC in clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, some studies reported that hASCs can increase Tregs population in the allogeneic rejection scenario, such as the solid organ transplantation, hematopoietic stem cell transplantation. In a study of MSCs therapy for clinical liver transplantation, the significant increase of Tregs percentage and the Tregs/Th17 ratio were observed 4 weeks after MSCs infusions . It is also accepted that adoptive transfer of ex vivo expanded Tregs efficiently inhibit CD8 + T‐cell tissue invasion and thus delay skin graft rejection, and IL25 can promote their function .…”
Section: Discussionmentioning
confidence: 99%